Use of global rice sustainability standards - CGIAR Research Program on Rice (2018)
The Sustainable Rice Platform (SRP) Standard for Sustainable Rice Cultivation is the world’s first voluntary sustainability standard for rice. The Standard defines a set of key requirements with different levels of performance allowing for a stepwise improvement and compliance process. Many of the over 80 SRP members are testing, adopting, and implementing the SRP standards in different parts of the world. Full details are available on the SRP website at: http://www.sustainablerice.org/Resources/#local-action.